2020
DOI: 10.1007/s10637-020-00914-5
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the vasopressin analog desmopressin for the management of bleeding in rectal cancer patients: results of a phase I/II trial

Abstract: Purpose The vasopressin analog desmopressin (dDAVP) is known to increase plasma levels of hemostatic factors, and preclinical studies in colorectal cancer models have demonstrated that it hampers tumor vascularization and metastatic progression. We evaluated safety and preliminary efficacy of dDAVP in rectal cancer patients with bleeding, before receiving specific oncologic treatment with surgery, chemotherapy and/or radiotherapy. Methods Patients with rectal cancer having moderate or severe rectal bleeding we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In animal studies, infusion of desmopressin during surgery appears to inhibit perioperative metastatic events and may impede micro-metastases that occurred before surgery (109,111). However, high doses of desmopressin have been used in human trials of desmopressin for cancer treatment: two 1 µg/kg intravenous doses (one just before surgery, one 24 h after surgery) in one study (109) and a maximum tolerated dose of 2x0.5 µg/kg/12 h in another (110).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In animal studies, infusion of desmopressin during surgery appears to inhibit perioperative metastatic events and may impede micro-metastases that occurred before surgery (109,111). However, high doses of desmopressin have been used in human trials of desmopressin for cancer treatment: two 1 µg/kg intravenous doses (one just before surgery, one 24 h after surgery) in one study (109) and a maximum tolerated dose of 2x0.5 µg/kg/12 h in another (110).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…After one month, the level of cytokeratin-19 transcript returned to the baseline detected before surgery. The next phase I/II trial (NCT01623206) demonstrated that dDAVP may be considered as a promising hemostatic agent in rectal cancer patients with bleeding [ 186 ]. After a short, two-day treatment with dDAVP most patients showed at least a partial hemostatic response while about 60% had complete absence of bleeding symptoms at fourth day after the treatment started.…”
Section: Vasopressinmentioning
confidence: 99%
“…A clinically validated dDAVP dose of 1 µg/kg i.v. was taken as the reference dose (15,(30)(31)(32) and multiplied by 12.3 for human to mice conversion (33). Mice equivalent dose was rounded down from 12.3 to 12 µg/kg i.v.…”
Section: In Vivo Osteosarcoma Xenograft Progressionmentioning
confidence: 99%
“…In a second phase I/II clinical trial, safety and symptom control were assessed in rectal cancer patients with bleeding. As a result, after 4 days of treatment initiation, complete hemostatic control and reduction of tumor vascular perfusion were achieved in the vast majority of patients ( 32 ). Despite dDAVP deployed interesting and promising anticancer activity as a repurposed agent in a variety of experimental and clinical settings, its potential therapeutic benefits in osteosarcoma were never evaluated.…”
Section: Introductionmentioning
confidence: 99%